Copper(I)‐Catalyzed Enantioselective Nucleophilic Borylation of Aliphatic Ketones: Synthesis of Enantioenriched Chiral Tertiary α‐Hydroxyboronates. Issue 23 (3rd May 2017) - Kubota, Koji; Osaki, Shun; Jin, Mingoo; Ito, Hajime
Abstract: A new method was developed for the first catalytic enantioselective borylation of aliphatic ketones. A variety of substrates reacted efficiently with bis(pinacolato)diboron in the presence of a copper(I)/chiral N‐heterocyclic carbene complex catalyst to furnish optically active tertiary α‐hydroxyboronates with moderate to high enantioselectivities (up to 94 % ee ). Notably, the product could be converted into the chiral tertiary alcohol derivative using a stereospecific boron functionalization process. The theoretical study of the mechanism for the enantioselectivity is also described. Abstract : Ketone functionalization : The first catalytic enantioselective borylation of ketones is presented. A variety of aliphatic ketones reacted efficiently with bis(pinacolato)diboron in the presence of a copper(I)/chiral N‐heterocyclic carbene complex to furnish the corresponding tertiary α‐hydroxyboronate esters with moderate to high enantioselectivities.